Impact evaluation of instream bar management using morphodynamic modelling - Yu, Qingcheng; Rennie, Colin; Slaney, Jonathan; Parsapour-Moghaddam, Parna (Université d'Ottawa | University of Ottawa, 2022)
The Bow River’s 2013 flood was the costliest natural disaster in the City of Calgary’s history. Flood-induced bar growth and subsequent riparian vegetation colonization at many locations has constricted the river channel, which increases flood risk. Although bar removal has been widely employed as a flood mitigation strategy, its effectiveness and associated impacts are still uncertain. This study employs Delft3D to develop a two-dimensional (2D) morphodynamic model in order to evaluate the impacts of a conventional plan of bar removal and a novel plan of bar realignment in terms of flood mitigation, aquatic habitat protection and river recreation realization. A hydrodynamic model was firstly developed and calibrated using post-flood spatially distributed velocimetry data. A morphodynamic model was then developed and validated using post-flood bed elevation survey data. Then, the future channel response and flood peak levels using different bar management plans were modelled and compared. Results show that appropriate bar realignment can protect aquatic habitat and provide river recreation opportunities while bar removal performs the better in terms of lowering the future flood peak level. The findings indicate that manipulation on instream bars has little morphological impact to downstream reach and creating a less obstructed channel is the fundamental strategy in flood mitigation.
Keywords: Morphodynamic modelling; Gravel bar; Bar removal; Bar realignment; Flood; Aquatic habitat